Greyscale image encoding and watermarking based on optical asymmetric cryptography and variational image decomposition. Issue 4 (23rd February 2019) - Su, Yonggang; Tang, Chen; Li, Biyuan; Qiu, Yue; Zheng, Tingyue; Lei, Zhenkun
ABSTRACT: In this paper, a novel greyscale image encoding and a watermarking scheme based on optical asymmetric cryptography and variational image decomposition (VID) are proposed. In this proposed scheme, the greyscale watermark is encoded into a noise-like pattern by the phase-truncated Fresnel transform (PT-FrT)-based optical asymmetric cryptography. The greyscale host image is decomposed into its cartoon part and texture part by the VID technique. After that, the encoded watermark is embedded into the host image's texture part by a discrete wavelet transform (DWT) based fusion approach. The proposed scheme can achieve a better watermark invisibility and a higher robustness by embedding the watermark into the host image's texture part. Additionally, the proposed scheme can achieve a high security, because the PT-FrT-based optical asymmetric cryptography can resist some common cryptographic attacks. The feasibility, robustness and security of the proposed scheme have been demonstrated by extensive experiments and comparison with other relevant image encoding and watermarking schemes.